Consciousness and Theory of Mind: a Common Theory? - Sebastián, Miguel Ángel (THEORIA. An International Journal for Theory, History and Foundations of Science, 2016)
Many philosophers and scientists have argued that the difference between phenomenally conscious states and other kind of states lies in the implicit self-awareness that conscious states have. Higher-Order Representationalist (HOR) theories, attempt to explain such a self-awareness by means of a higher-order representation. Consciousness relies on our capacity to represent our own mental states, consciousness depends on our Theory of Mind. Such an ability can, at least conceptually, be decomposed into another two: mindreading and metacognition. In this paper I will argue that consciousness cannot depend on mindreading. The tenability of HOR theories depends, therefore, on the relation between mindreading and metacognition. I analyze several views on such a relation and argue that none of them seem to be a plausible option for HOR theories.